Nexus of Electricity Demand, Circular Debt and Economic Progress: An Evidence from Pakistan - Anwar, Awais; Arshed, Noman; Ahmad, Shabir; Hayat, Naveed (iRASD Journal of Economics, 2023)
In the context of Pakistan, this research examines circular debt and energy usage effects on per capita income. It uses quarterly data from 2005 to 2020 and an autoregressive distributed lag model to look at the link over the short- and long-term. According to the empirical study, whereas circular debt has a long-term significant negative association with per capita income, it has a significant positive link with per capita income in the short term. This demonstrates how using power contributes to economic expansion. Additionally, a rise in circular debt reduces per capita income in the near term, but the long-term convergence of the system to equilibrium is confirmed by the error correction term’s considerable negative value. In addition, study shows that consistent provision of electricity with the help of new technologically advanced electricity plants would help in attaining high economic growth.